Influence of Alkaline Additives and Buffers on Mineral Trapping of CO2 under Mild Conditions. Issue 3 (5th January 2018) - Schütz, Marta K.; Lopes, Natália F.; Cenci, Angélica; Ketzer, João Marcelo M.; Einloft, Sandra; Dullius, Jeane; Ligabue, Rosane
Abstract: Carbon dioxide (CO2 ) gas is the main contributor to climate change. CO2 storage in underground brines and oil‐field brines by mineral trapping has been considered as a promising alternative in order to reduce CO2 emissions. However, permanent storage of CO2 in stable carbonate minerals is greatly dependent on brine pH, being favored over an alkaline pH. The effect of alkaline additives (NaOH, KOH, CaO) and buffer solutions (NaHCO3 /NaOH, Na2 HPO4 /NaOH, NH4 Cl/NH4 OH) on the mineral trapping of CO2 under mild conditions using a synthetic brine is investigated. The results indicate that both NaOH+NH4 Cl/NH4 OH and KOH+NH4 Cl/NH4 OH mixtures promote precipitation mainly of calcium carbonate (CaCO3 ). Abstract : CO2 storage using brines is a promising technology to mitigate the climate change. Mineral trapping of CO2, however, is favored over an alkaline pH. Carbonation of a synthetic brine upon rising the pH by adding alkaline additives and buffer solutions was investigated under mild conditions. The combination of an alkaline additive and buffer is suitable to precipitate calcium carbonate.